2020
DOI: 10.1101/2020.12.13.20248129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Mobility Data to Understand and Forecast COVID19 Dynamics

Abstract: Disease dynamics, human mobility, and public policies co-evolve during a pandemic such as COVID-19. Understanding dynamic human mobility changes and spatial interaction patterns are crucial for understanding and forecasting COVID-19 dynamics. We introduce a novel graph-based neural network(GNN) to incorporate global aggregated mobility flows for a better understanding of the impact of human mobility on COVID-19 dynamics as well as better forecasting of disease dynamics. We propose a recurrent message passing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…Few other studies have exploited mobility data, such as those generated by Google. For example, Wang et al [ 27 ] have shown that is of paramount importance to understand dynamic changes in human mobility, social networks and spatial interaction trends to better predict the still ongoing COVID-19 pandemic. Authors were able to demonstrate that incorporating Google-outputted mobility data resulted in a significantly higher predictive power of COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Few other studies have exploited mobility data, such as those generated by Google. For example, Wang et al [ 27 ] have shown that is of paramount importance to understand dynamic changes in human mobility, social networks and spatial interaction trends to better predict the still ongoing COVID-19 pandemic. Authors were able to demonstrate that incorporating Google-outputted mobility data resulted in a significantly higher predictive power of COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…This question is often formulated as an appropriate variant of the facility location problem, which is wellstudied in the operations research literature (see Related Work). In our paper, we introduce a new variant that follows a recent line of work on integrating the mobility patterns of the population into disease models [Chang et al, 2021;Wang et al, 2020]. As is standard, we will use the distance from a vaccination center as the metric for defining accessibility.…”
Section: Preliminariesmentioning
confidence: 99%
“…Human mobility has been analyzed using multiple kinds of data, including cellphone pings [24], call detail records [15], social media geotags [47], aggregated mobility flows [42], and synthetic populations [40]. While previous research has focused on diverse topics, such as finding general patterns and laws of human mobility [18], analyzing traffic [4,31], or studying human movements during disasters [24,33], with COVID-19 and other epidemics, the emphasis has largely been on using mobility data to do epidemic forecasting.…”
Section: Related Workmentioning
confidence: 99%
“…Google released a public mobility index showing the change in mobility by region and activity type [16]. Google also shared aggregated mobility flow data with some research partners in a privacy-preserving way [42]. Similarly, Cuebiq released a mobility index and shared cellphone ping data with some research partners, also in a privacy-preserving way [11].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation